Efecto de alternancia de presión en el equilibrio y separación de mezclas azeotrópicas tetrahidrofurano - agua - Asto Fuentes, Patricia (2019)
In this thesis the effect of the pressure alternation on the displacement of the minimum boiling point THF - water system azeotrope in the interval of 1 and 10 atm was analyzed by Chemcad simulator V.7.1.2. The displacement of the boiling point was possible to predict it considering the NRTL model for the calculation of the activity coefficient for the liquid phase. The modular sequential method implemented in CHEMCAD V7.1.2 and for the case of two rigorous SCDS in series columns, operating the first at 1 atm and the second at 10 atm, both of 12 plates and with RR of 2,54 the first and 0,70 the second, allowed to recover the THF with the 99% mol purity proposed in the configuration of the rigorous modules simulator. Other alternations intervals pressure less than 1 to 10 only allowed to recover values lower than 65.79% mol of the THF fed in the first tower. Likewise. increasing the number of stages of the first and second towers from 12 to 16 and their variation of the feed points to the towers, had no effect on the recovery improvement of the THF. The recovery in question requires a total heat consumption of 13197 MJ / h, corresponding to 10060 MJ / h for tower 1 and 3137 MJ / h for the second tower